Media use and behavioral disorders among Saudi Arabian children - Salmah Alghamdi; Duaa Bawageeh; Hessa Alkhaibari; Amwaj Almutairi; Shoug Aljuhani (Belitung Raya Foundation, Indonesia, 2021)
Background: Despite children’s frequent use of electronic devices, there is a lack of evidence showing how such media use influences their behavior. Objective: This study was to assess the relationship between media use and behavior among a sample of children aged three to 11 years. Methods: This was a descriptive cross-sectional study. An electronic self-administered questionnaire was completed from January 2020 to March 2020 by a convenience sample of 234 parents with healthy children in the target age group. Descriptive statistics and One-Way Analysis of Variance (ANOVA) were used for data analysis. Results: There was no significant difference in children's behavior according to the type of media [F(3, 230) = 1.673, p = 0.174]. In contrast, there was a significant difference in children's behavior according to hours per day of media use [F(4, 229) = 2.701, p = 0.031]. The most commonly used mobile device was the smartphone (n = 87, 37.2%). More than a quarter of the children spent three hours a day using media. Conclusions: This study offers insight into associations between children’s frequent media use and their behavior. The results suggest that the significant factor associated with behavioral problems is not the type of media but the time spent using it. Nurses are encouraged to use these findings in developing educational programs that raise awareness among parents and children regarding the consequences of excessive media use.